Hydrogen induced slowdown of spallation in high entropy alloy under shock loading - Xie, Z.C.; Li, C.; Wang, H.Y.; Lu, Chunsheng; Dai, L.H. (2021)
Hydrogen embrittlement is ubiquitous in metals and alloys exposed to hydrogen, which has been extensively studied over a century. In contrast to traditional alloys, mechanisms of hydrogen embrittlement under shock loading are poorly understood, especially in recently emerging multi-principle element and chemically disordered high entropy alloys (HEAs). By using a specially designed double-target technique, an unexpected phenomenon of hydrogen-retarded spallation was observed in CrMnFeCoNi HEA under plate impact loading. To reveal the underlying mechanism, a trans-scale statistical damage mechanics model was developed based on microstructural characterization and first principles calculations. The hydrogen-retarded nucleation of micro-voids is attributed to hydrogen-vacancy complexes with high migration energy, while formation of nano-twins with high resistance reduces their growth rate. These results shed light on the better understanding of hydrogen embrittlement in chemically complex HEAs.